Relationship Between the Posture of Lifting and Lowering Rice Sacks and Musculoskeletal Complaints Rice Transport Workers at PT X - Maria, Maria Winona Kidi; Imam Santoso; Juanda (Jurnal Kesehatan Cendikia Jenius, 2024)
Incorrect working postures while lowering and lifting rice sacks for extended periods can lead to muscle and bone problems, particularly affecting the skeletal muscles. This work involves repetitive movements or is performed in specific positions such as bending, tilting the neck, and standing still for long durations. Musculoskeletal disorders are generally caused by non-ergonomic work postures, long working hours, and monotonous, repetitive movements. This study aims to determine the relationship between work posture in lowering and lifting rice sacks and musculoskeletal complaints. Data collection methods included interviews, questionnaires, and the REBA observation sheet to assess work posture, as well as the Nordic Body Map observation sheet for musculoskeletal complaints, with a sample size of 30 rice transport workers. The statistical test used was Spearman's rank correlation. The results indicate a significant relationship (p-value = 0.003, r = 0.527). It can be concluded that there is a significant relationship between work posture while lifting rice sacks and musculoskeletal complaints among the workers at PT X. It is recommended that workers reduce the load they carry and use assistive devices such as trolleys or lifting equipment to lessen physical workload and reduce stress on their bodies.